THE DIFFERENCE BETWEEN INQUIRY AND DIRECT LEARNING MODEL USING DRILL METHOD TOWARDS STUDENTS LEARNING ACHIEVEMENT IN CHEMISTRY BY OBSERVING MEMORIZING SKILL IN STUDENTS OF CLASS XI ON RATE OF REACTION TOPIC IN SMK NEGERI 17 SAMARINDA - Nurlaili -; Galuh Hayu Widyaningrum (PROSIDING SEMINAR KIMIA, 2015)
This study aims to find out: (1) the difference of implementation of inquiry and direct learning model using drill method towards learning achievement in chemistry on rate of reaction topic in SMK Negeri 17 Samarinda, (2) the difference between students who have high memorizing skill in class which utilizes inquiry learning model and class which utilizes direct learning through drill method and students who have low memorizing skill in class which uses inquiry learning model and class which uses direct learning through drill method towards learning achievement on rate of reaction topic in SMK Negeri 17 Samarinda. The population in this research is all students of class XI Pharmacy in SMK Negeri 17 Samarinda, while the samples being taken is class XI Pharmacy 2 and XI Pharmacy 3, each has 25 students. XI Pharmacy 2 is the class that uses inquiry learning model while XI Pharmacy 3 implements direct learning through drill method. Data collecting technique being used in this research is the test technique. The result is then analyzed by using t-test. From the result, it can be concluded that: (1) there is no difference between the implementation of inquiry and direct learning through drill metthod towards learning achievement on rate of reaction topic in SMK Negeri 17 Samarinda, (2) there is difference in learning achievement between students who have high memorizing skill in class using inquiry learning model with class using direct learning through drill method and there is no difference in learning achievement between students who have low memorizing skill in class using inquiry learning model with class using direct learning through drill method.